2019
DOI: 10.1002/mrc.4936
|View full text |Cite
|
Sign up to set email alerts
|

Purity determination of a new antifungal drug candidate using quantitative 1H NMR spectroscopy: Method validation and comparison of calibration approaches

Abstract: Quantitative nuclear magnetic resonance (qNMR) is an analytical technique that offers numerous advantages in pharmaceutical applications including minimum sample preparation and rapid data collection times with no need for response factor corrections, being a powerful tool for assaying drug content in both drug discovery and early drug development. In the present work, we have applied qNMR, using both the internal standard and the electronic reference to access in vivo concentrations 2 calibration methods, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The remaining 30 % of the mass comprises impurities. The study revealed that equivalent results were observed with both IS and ERETIC-2 calibration approaches yield the same result [67] .…”
Section: Quantitative Methods Validation Of Drugs and Excipients Using Nmr Techniquesupporting
confidence: 54%
See 2 more Smart Citations
“…The remaining 30 % of the mass comprises impurities. The study revealed that equivalent results were observed with both IS and ERETIC-2 calibration approaches yield the same result [67] .…”
Section: Quantitative Methods Validation Of Drugs and Excipients Using Nmr Techniquesupporting
confidence: 54%
“…In the experiment, 5 mg of acetanilide and 12 mg of RI76 (fig. 1) were accurately weighed and dissolved in 600 µl of Deuterated dimethyl sulfoxide (DMSO-d 6 ), which was accurately transferred to NMR tubes for evaluating the purity of RI76 [67] .…”
Section: Quantitative Methods Validation Of Drugs and Excipients Using Nmr Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Simulations based on the target structure bring a greater chance of success for drug development in less time [136] (Figure 3). The target prediction for drug discovery can be based on structural models available in databases, resulting from X-ray crystallography or NMR spectroscopy [137]. The best binding sites are identified by computational tools, according to physical-chemical properties, and thus the docking for selection of inhibitors can start by virtual screening [138].…”
Section: In Silico Strategy For New Antifungal Developmentmentioning
confidence: 99%
“…RI76 increased the survival of Galleria mellonella larvae infected with Candida albicans to 81.3%, and it also proved to be effective in the murine model of oral and systemic candidiasis when tested at 10 mg/kg (Cruz et al, 2018). The purity of RI76 synthesized in‐house was assessed by quantitative nuclear magnetic resonance using two different calibration methods, which provided similar results for RI76 content (Franco, Braga, Oliveira, & César, 2020). Based on these results, RI76 was selected as a possible drug candidate.…”
Section: Introductionmentioning
confidence: 98%